IDH1/IDH2 Inhibition in Acute Myeloid Leukemia - Cerchione, Claudio; Romano, Alessandra; Daver, Naval; DiNardo, Courtney; Jabbour, Elias Joseph; Konopleva, Marina; Ravandi-Kashani, Farhad; Kadia, Tapan; Martelli, Maria Paola; Isidori, Alessandro; Martinelli, Giovanni; Kantarjian, Hagop (Frontiers in Oncology, 2021)
In the recent years, the emerging pathogenic role of mutations in isocitrate dehydrogenases (IDH) 1 and 2, affecting approximately 20% of patients with acute myeloid leukemia (AML), lead to the development of an individualized treatment strategy. Targeting IDH mutations in AML is a biologically informed and rational strategy to promote clinical responses, primarily through differentiation and maturation of the malignant clone. Phase I/II trials have shown evidence of safety, tolerability, and encouraging evidence of efficacy of two small molecule inhibitors targeting IDH2 and IDH1 gene mutations, respectively enasidenib and ivosidenib. In this review, the contribution of IDH1/IDH2 mutations in leukemogenesis and progress of targeted therapeutics in AML will be highlighted.